Permasalahan dan Peluang Pendidikan di SMK pada Era Teknologi Digital - Maenuddin Bustanil Syah; Asrowi Asrowi; Deny Tri Ardianto (Teknodika, 2019)
The era of digital technology in education is developing rapidly in the use of innovative media in the learning process to produce competent and competitiveness graduates. This study aims to analyze the development of interactive multimedia as a need for the learning process of graphic design printing in the Digital Technology Era. This study uses descriptive qualitative method with the data collection techniques of observations, interviews, and documentation. This study was conducted at SMK Negeri 3 Parepare. The subjects of the study consisted of 61 students and a graphic design teacher. First, the results from the questionnaires show that the current learning process has not been able to motivate students, so it is expected the interactive multimedia can facilitate the students to understand and improve their multimedia competence. Second, based on the interview with the graphic design teacher, the teacher also expects the innovation of learning, specifically interactive multimedia, as a support for the learning process to improve the students’ multimedia competence. This study implies that the interactive multimedia needs to be developed as a support for the learning process to improve students’ multimedia competence